The Difference of Second/ Foreign Language Acquisition and Learning for Adults and Children (A Qualitative Study on Steinberg’s Research (1982 and 1993)) - Arifin, Win Listyaningrum (Journal of English Teaching and Learning Issues, 2020)
This paper is based on the research by Steinberg in 1982 and 1993 to answer the question of how children and adults control second/foreign languages with the focus on giving more reasonable answers whether the children are better than adults in the mastery. The process of obtaining second language can be from the natural/social/acquisition and from class/learning. The learner's internal factors such as the role of the first language, motivation, and attitudes are also very important in determining the success of second language acquisition. Steinberg et al. try to draw the conclusion that the decrease in memory power for learners is associated with age. Age cannot be a benchmark for the success rate of mastering a second/foreign language other than mother tongue as long as the involved people have desire to use the foreign language or the second language for the purpose of integrating and socializing.